The rise and fall of the Rhodesian economy - Bond, Patrick (My University, 1993)
The period of the Rhodesian Front party's Unilateral Declaration of Independence (UDI) is sometimes described as providing a "hot-house" atmosphere for economic development, a characterisation which stems from extraordinary rates of growth from 1966-1974 as well as from the various barriers to free financial flows erected by the state.1 These barriers imposed a condition of semi-autarchy on the financial circuit of capital, which in turn had implications for accumulation and uneven geographical and sectoral development. The most significant of these may be that the hot-house financial environment exacerbated capitalist boom-bust tendencies, in an economic context which was already deteriorating due largely to overproduction in relation to the small size of the local market, as well as to exogenous factors. When a classic crisis of "overaccumulation"2 of capital emerged in the mid 1970s, the effect on the social and political formation was formidable, and indeed has not been resolved to this date. One reason why different attempts to deal with the crisis have not been successful is that economic development has generally been viewed in static and aspatial terms, with scant regard for the complex roles of space and of time. This, then, is a key challenge to the paper: while constructing an empirically- and theoreticallyinformed argument about the Rhodesian UDI period, I attempt to analyze spatial and temporal features that shed brighter light on limits to the economy's development.
African Studies Seminar series. Paper presented 22 February, 1993
Keywords: Zimbabwean economy (1966-74)